PRAKTEK KEKUASAAN DAN DOMINASI GURU DI DALAM KELAS DITINJAU DARI STRUKTUR WACANA PEDAGOGIK PEMBELAJARAN BAHASA INGGRIS - Hamzah, Hamzah; Ningsih, Kurnia (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2015)
This study is aimed at exploring the way the English teachers at senior high schools exercise power and domination during the teaching and learning process. Conversation analysis and critical discourse analysis were used to analyze the data. The data were generated from thirty transcripts of classroom interaction comprising of two academic hour session for each transcript. The findings of this study revealed that the English teacher still exercised strong power and domination in the classroom. Most exchanges were initiated by the teacher (93%), and the students involvements were limited to providing responses in accordance with the information initiated by their teacher. The teachers’ domination was also seen in the length of the turns. The teachers normally had extended turn comprising one clause or more, while students’ contributions were normally short consisting of one word, one phrase, and one clause was the longest in each turn. Beside the two indicators, the teachers’ power and domination were seen in controlling the topic, giving instruction, asking close questions and providing correction. Key words: conversation, classroom discourse, power and domination